Research Progress on Nanotechnology-Driven Enzyme Biosensors for Electrochemical Detection of Biological Pollution and Food Contaminants - Liang Qu; Xue Zhang; Yanhong Chu; Yuyang Zhang; Zhiyuan Lin; Fanzhuo Kong; Xing Ni; Yani Zhao; Qiongya Lu; Bin Zou (Foods)
Electrochemical biosensors have attracted widespread attention from researchers due to their simple and rapid operation. Recent advancements in nanobiotechnology have further enhanced their performance, with nanomaterials like graphene, carbon nanotubes, and metal nanoparticles being widely used as carriers for immobilizing enzymes, cells, and DNA molecules. These materials improve stability, sensitivity, and selectivity, making biosensors more effective. This article reviews the introduction, principles, and classification of enzyme-based electrode sensors, as well as their research and application progress in the detection of food risk factors (including foodborne pathogens, biotoxins, drug residues, food additives, allergens, etc.). It also explores future prospects, including advancements in nanotechnology and enzyme immobilization techniques, highlighting their potential in food safety and beyond.